Assessing the Environmental and Economic Impact of Smart Grid Integration in Renewable Energy Management - Henry Henry; Konita Lutfiyah; Harry Agustian; Nicholas Lachlan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
The global transition to renewable energy aims to reduce environmental impacts and combat climate change, yet challenges arise due to the intermittent nature of renewable sources, complicating their integration into traditional power grids and requiring advanced management solutions. Smart grid technology presents promising capabilities to optimize renewable energy management, promoting both environmental sustainability and economic efficiency. This study evaluates the environmental and economic impacts of smart grid integration, fo- cusing on carbon emission reductions, enhanced energy efficiency, and cost savings for energy providers and consumers. Using Structural Equation Modeling via SmartPLS, data were collected and analyzed from various stakeholders engaged in renewable energy and smart grid applications, allowing a detailed assessment of the relationships between smart grid integration, environmental outcomes, and economic benefits. Results indicate that smart grid integration significantly reduces carbon emissions and improves energy efficiency by over 30% while economically, it yields substantial cost savings, cutting operational expenses by up to 25% over time. The SmartPLS analysis confirms a positive relationship between smart grid deployment and both environmental and economic outcomes, highlighting that smart grids not only support emission reductions but also deliver considerable financial benefits in renewable energy management. These findings offer important insights for policymakers and industry stakeholders, emphasizing the role of smart grids in advancing sustainable and economically viable global energy systems.